This preview shows pages 1–5. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: EECS 20 Fall 2010 Homework 4 solutions HW4.1 The forward gain of the inner loop is F ( ! ), and its loop gain is A ( ! ) B ( ! ) F ( ! ). The closed loop frequency response of the inner loop is therefore Forward Gain 1 Loop Gain = F ( ! ) 1 A ( ! ) B ( ! ) F ( ! ) : Call this G ( ! ). The forward gain of the outer loop is G ( ! ) and its loop gain is P ( ! ) G ( ! ). This H ( ! ) = G ( ! ) 1 + P ( ! ) G ( ! ) = F ( ! ) 1 A ( ! ) B ( ! ) F ( ! ) 1 + P ( ! ) F ( ! ) 1 A ( ! ) B ( ! ) F ( ! ) = F ( ! ) 1 + ( P ( ! ) A ( ! ) B ( ! )) F ( ! ) : 1 HW4.2 (a) F ( ! ) = X n 2 Z f ( n ) e in! = X n ;n odd n e in! = e i! 1 X l =0 ( 2 e i 2 ! ) l = e i! 1 2 e i 2 ! : (b) G ( ! ) is recognized as the frequency response of the unit delay. Its impulse response is therefore g ( n ) = ( n 1) : This can be veri ed by checking that e i! = X n 2 Z ( n 1) e in! : (c) The forward gain is F ( ! ) = e i! 1 2 e i 2 ! : 2 (d) The loop gain is kG ( ! ) F ( ! ) = k e i 2 ! 1 2 e i 2 ! : (e) The closed loop frequency response is H ( ! ) = Forward Gain 1 Loop Gain = F ( ! ) 1 + kG ( ! ) F ( ! ) = e i! 1 2 e i 2 ! 1 + k e i 2 ! 1 2 e i 2 ! = e i! 1 ( 2 k ) e i 2 ! : (f) From the formula for H ( ! ), we see that h ( n ) = unless n 0 and n is odd if n = 1 ( 2 k ) if n = 3 ( 2 k ) 2 if n = 5 etc. : Thus X n 2 Z j h ( n ) j = j j 1 X l =0 j 2 k j l : This means that X n 2 Z j h ( n ) j < 1 () j 2 k j < 1 : Thus the closed loop system is BIBO stable if and only if 2 k < 1 and 2 k > 1 ; i.e., if and only if 1 < k < + 1 : 3 HW4.3 (a) < x; x > = n X i =1 x ( i ) x ( i ) = n X i =1 j x ( i ) j 2 : This is a sum of nonnegative real numbers, hence it is real and nonnegative. Further, < x; x > equals zero if and only if each j x ( i ) j 2 equals zero, i.e. if and only if each x ( i ) equals zero, i.e. if and only if x is the zero vector. (b) < y; x > = n X i =1 y ( i ) x ( i ) = n X i =1 ( x ( i ) y ( i )) = ( n X i =1 x ( i ) y ( i )) = ( < x; y > ) : (c) < x 1 + x 2 ; y > = n X i =1 ( x 1 ( i ) + x 2 ( i )) y ( i ) = n X i =1 x 1 ( i ) y ( i ) + n X i =1 x 2 ( i ) y ( i ) = < x 1 ; y > + < x...
View
Full
Document
This note was uploaded on 12/24/2011 for the course ELECTRICAL 20 taught by Professor Babak during the Spring '11 term at University of California, Berkeley.
 Spring '11
 BABAK
 Frequency

Click to edit the document details